fac-[RuCl3(no)(dppb)] (I) and mer-[RuCl3(NO)(diop)] (II) complexes: Syntheses, characterization and x-ray structures - Von Poelhsitz, Gustavo [UNESP]; De Araujo, Màrcio Perez [UNESP]; De Oliveira, Luiz Antonio Andrade [UNESP]; Queiroz, Salete Linhares; Ellena, Javier; Castellano, Eduardo Ernesto; Ferreira, Antonio Gilberto; Batista, Alzir Azovedo [UNESP] (Elsevier, 2002)
The fac-[RuCl3(NO)(dppb)] complex I has been prepared from solution of the correspondent mer isomer in refluxing methanol (dppb = 1,4-bis(diphenylphosphino)butane). The mer-[RuCl3(NO)(diop)] (II) has been obtained from the mer-[RuCl3(diop)(H2O)] by bubbling NO for 1 h in dichloromethane (diop = 2S,3S-O-isopropylidene-2,3-dihydroxy-1,4-bis(diphenylphosphino)butane). The complexes have been characterized by microanalysis, cyclic voltammetry (CV), IR and 31P{1H} NMR spectroscopies. The crystal and molecular structures of these two compounds have been determined from X-ray studies. The mer-[RuCl3(NO)(dppb)] isomer III was characterized in solution by NMR spectra (31P{1H}, 1H{31P}, 31P-1H HETCORR, COSY 1H-1H, HMQC 1H-13C and HMBC 1H-13C). © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Diop; Dppb; Nitrosyl complexes; NMR spectra; Ruthenium(II); X-ray structures; isopropylidene 2,3 dihydroxy 1,4 bis(diphenylphosphino)butane; metal complex; methanol 1,4 bis(diphenylphosphino)butane; ruthenium complex; unclassified drug; analytic method; catalysis; chemical analysis; complex formation; nuclear magnetic resonance; phase transition; structure analysis; synthesis; X ray analysis